A literatura e leitura no valor educativo para as crianças - Silva, Graziella Bueno da (Universidade Federal do Tocantins, 2019)
Every educator concerned Every educator concerned with fulfilling his social role satisfactorily seeks to acquire knowledge that guides him in promoting the full development of the student. The present work aims to bring a reflection on the literature for children, their conceptions and the aspects that permeate the teaching process of reading in the Brazilian school. However, they seek to present the concepts and the diversities about reading and writing, thus being the first steps for learning, the acquisition of new skills that have importance in the formation of a reader. That brings growth in the educational and social character of reading and its importance in the life of man; besides the conception of literature for children and their importance in the formation of the personality of each person. We used articles from the SciElo, PubMed, Google Academic, and Electronic Journals for the academic scientific background. Reading is expected to play a very important role in the life of the reader, from the first steps, to the formation of the personality of the reader. Finally, it is concluded that for the formation of the habit of reading, it is necessary, from the first years of student life of the individual, a joint action of parents and educators in the sense of bringing the child closer to books; which is possible through the recognition of reading, and by extension of the literature, as an essential element in the development of a society.